Perbandingan Rasio Keuangan dan Risiko Kebangkrutan Sebelum dan Sesudah Pandemi Pada Healthcare Firms di Bursa Efek Indonesia - Clara Valencia; Yuliyani ,; Lu'lu'ul Jannah (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
The country of Indonesia experienced the Covid-19 pandemic in 2020. This condition has an impact on many sectors, one of which is the health sector. This study examines the Healthcare companies on the Indonesia Stock Exchange. This study aims to determine the comparison of financial ratios and bankruptcy risk experienced by Healthcare companies before and after the pandemic. The sample companies are 21 Healthcare companies on the IDX. The variables used are the liquidity ratio proxied by the Current Ratio (CR); leverage ratio proxied by Debt to Assets Ratio (DR); activity ratio proxied by Fixed Assets Turnover Ratio (FATO); profitability ratio proxied by Gross Profit Margin (GPM) and bankruptcy risk as proxied by Altman Z-Score. Paired Sample T-test is an analytical technique used to see the condition of the data with a norm distribution and the Wilcoxon Sign Rank Test for data that is not normally distributed. The results of this study explain that all the variables studied have no differences before and after the pandemic. Of the 21 samples of Healthcare companies on the IDX between 2019-2020, there were two companies in the red zone (bankruptcy) and one company in the vulnerable (grey zone). So it can be concluded that on average, Healthcare companies on the IDX have not experienced a decline or have difficulty maintaining their companies